2012
DOI: 10.1002/bsl.2014
|View full text |Cite
|
Sign up to set email alerts
|

Does Risk Assessment Make a Difference? Results of Implementing the SAVRY in Juvenile Probation

Abstract: An effective approach to reducing recidivism is, first, to identify a youth's risk of reoffending and then to match the intensity of interventions to that risk level. This pre–post quasi‐experimental, prospective study compared 247 (pre) with 217 (post) adjudicated youths to examine the implementation of the Structured Assessment of Violence Risk in Youth (SAVRY) and its effects on case management practices in Louisiana's Caddo parish probation office. The results indicated that placement rates dropped by 50%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 42 publications
2
64
0
Order By: Relevance
“…Indeed, there is evidence that probation officers' individual knowledge and beliefs about RNR principles (Ballucci, 2012;Haas & De Tardo-Bora, 2009;Luong & Wormith, 2011;Vincent et al, 2012) and about the validity of the tools used in their risk-need assessment practice (Miller & Maloney, 2013) impact implementation of risk-needs assessment and case management.…”
Section: Research On Implementationmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, there is evidence that probation officers' individual knowledge and beliefs about RNR principles (Ballucci, 2012;Haas & De Tardo-Bora, 2009;Luong & Wormith, 2011;Vincent et al, 2012) and about the validity of the tools used in their risk-need assessment practice (Miller & Maloney, 2013) impact implementation of risk-needs assessment and case management.…”
Section: Research On Implementationmentioning
confidence: 98%
“…It has been applied in Canada, the United States, Britain, Europe, Australia, and New Zealand and is the basis for many empirically derived rehabilitative treatment and case-management programs in these countries. Evidence indicates that agencies that adopt these structured and validated RNR-based assessment systems demonstrate greater reductions in recidivism (Andrews & Bonta, 2010) and more appropriate allocation of resources for their clients (Vincent, Guy, Gershenson, & McCabe 2012) than those that do not, although it may be the structured nature of the intervention that takes place, rather than the model's principles per se, that account for these positive results (e.g., Duncan, Miller, Wampold, & Hubble, 2010).…”
mentioning
confidence: 98%
“…Given that one common use of the SAVRY is to aid in post‐adjudication intervention and supervision classification (Borum et al, ), evidence of an association among pre‐disposition SAVRY risk ratings and probation outcomes provides additional support for the continued use of the SAVRY at this stage of the juvenile justice system. Recently, Vincent, Guy, Gershenson, and McCabe () conducted a study to determine whether implementation of the SAVRY at post‐adjudication influences the ways in which youth are handled in the juvenile justice system. They reported that after implementation of the SAVRY there was a 50% reduction in out of home placements of adjudicated juvenile offenders, a 30% reduction in the use of intensive probation supervision, and a shift in service allocation where service referrals for high risk offenders increased and referrals for low risk offenders decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing risk assessment with RNR principles can conserve resources for juvenile justice systems and improve outcomes for youth while still protecting public safety. However, the impact of risk assessment will ultimately be based on how well it is implemented and a site's individual characteristics (Vincent et al, 2012a). Quality implementation, quality assurance, and buy-in from stakeholders are all crucial to successfully implement risk assessment tools and principles in juvenile systems settings.…”
Section: Risk-needs-responsivity (Rnr) Principlesmentioning
confidence: 99%